2018
DOI: 10.3390/genes9070361
|View full text |Cite
|
Sign up to set email alerts
|

GADD45B as a Prognostic and Predictive Biomarker in Stage II Colorectal Cancer

Abstract: GADD45B acts as a member of the growth arrest DNA damage-inducible gene family, which has demonstrated to play critical roles in DNA damage repair, cell growth, and apoptosis. This study aimed to explore the potential relationship between GADD45B expression and tumor progression and evaluate the clinical value of GADD45B in stage II colorectal cancer (CRC). The expression patterns and prognostic value of GADD45B in CRC were analyzed based on The Cancer Genomic Atlas (TCGA). GADD45B expression features of 306 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…In fact, this difference was not surprising because TCGA analysis was not always consistent with the experimental data. And the similar inconsistency between TCGA analysis and the experimental results had been reported before, which indicates that large numbers of samples or more patient cohorts are possibly helpful to further verify the prognostic role of Dyrk3 in HCC patients in future studies.…”
Section: Discussionsupporting
confidence: 60%
“…In fact, this difference was not surprising because TCGA analysis was not always consistent with the experimental data. And the similar inconsistency between TCGA analysis and the experimental results had been reported before, which indicates that large numbers of samples or more patient cohorts are possibly helpful to further verify the prognostic role of Dyrk3 in HCC patients in future studies.…”
Section: Discussionsupporting
confidence: 60%
“…Higher expression of GADD45B was an independent factor for shorter disease-free survival in our internal dataset and shorter overall survival in the TCGA cohort. Likewise, high GADD45B protein expression was an independent marker of poorer prognosis in stage II colorectal cancer and a potential marker to indicate post-operative chemotherapy (71). In thyroid cancer, an accurate recurrence predictive biomarker could aid in the de-intensification of the treatment in low risk patients (72).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between GADD45B expression and colorectal cancer progression has been recently investigated, and the results showed that overexpression of GADD45B is associated with poorer prognosis for CRC patients both in overall survival and disease-free survival and that, regarding protein levels, GADD45B was gradually upregulated in normal mucosa, primary tumors, and liver metastases tissues in ascending order, with a prognostic role in terms of progression. The authors underlined the significant longer overall survival and disease-free survival among patients with low GADD45B expression pointing at the high expressor-subgroup as one which might benefit from adjuvant chemotherapy [ 60 ].…”
Section: Resultsmentioning
confidence: 99%